2019
DOI: 10.1093/mnras/stz2869
|View full text |Cite
|
Sign up to set email alerts
|

Architectures of exoplanetary systems – I. A clustered forward model for exoplanetary systems around Kepler’s FGK stars

Abstract: Observations of exoplanetary systems provide clues about the intrinsic distribution of planetary systems, their architectures, and how they formed. We develop a forward modeling framework for generating populations of planetary systems and "observed" catalogs by simulating the Kepler detection pipeline (SysSim). We compare our simulated catalogs to the Kepler DR25 catalog of planet candidates, updated to include revised stellar radii from Gaia DR2. We constrain our model based on the observed 1-D marginal dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
159
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(164 citation statements)
references
References 110 publications
4
159
0
1
Order By: Relevance
“…When using the Dirichlet prior, the observed number of M dwarf planet candidates is also consistent with as few as half of M dwarfs hosting planetary systems. Recently, He et al (2019) investigated the architectures of planetary systems around Sun-like (FGK) stars with a clustered point process model built in the same SysSim framework as this study. He et al (2019) report a 68.3% credible interval for the multiplicity of 2.28 +0.94 0.53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When using the Dirichlet prior, the observed number of M dwarf planet candidates is also consistent with as few as half of M dwarfs hosting planetary systems. Recently, He et al (2019) investigated the architectures of planetary systems around Sun-like (FGK) stars with a clustered point process model built in the same SysSim framework as this study. He et al (2019) report a 68.3% credible interval for the multiplicity of 2.28 +0.94 0.53 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, He et al (2019) investigated the architectures of planetary systems around Sun-like (FGK) stars with a clustered point process model built in the same SysSim framework as this study. He et al (2019) report a 68.3% credible interval for the multiplicity of 2.28 +0.94 0.53 . Since this is less than the in-tegrated rate of M dwarf planets (for both out priors), even assigning every M dwarf such a planetary system would not be sufficient to explain the number of M dwarf planets detected by Kepler.…”
Section: Discussionmentioning
confidence: 99%
“…We do not apply an additional multiplicative factor representing the fraction of stars with planets -e.g. that there exists a population of stars with no planets in excess of a Poisson distribution, as is sometimes done in the literature (Mulders et al 2018;Zhu et al 2018;He et al 2019). In other words, we effectively assume the fraction of stars with planets per region is unity, and that the average number of stars per planet per region holds for all planets and that the individual number of planets per star per region follows a Poisson distribution which can include zero planets (see also 4).…”
Section: Drawing Planets To Create Populationsmentioning
confidence: 99%
“…By assuming planets in multi-planet systems are in coplanar orbits, Fressin et al (2013) and Petigura et al (2013) have found over 50% of Sun-like stars have Kepler -like planets (F p > 0.5). Recently, Zhu et al (2018), Mulders et al (2018), and He et al (2019) have modified the F p estimate by taking into account non-coplanar planetary systems.…”
Section: Introductionmentioning
confidence: 99%